Response to Novelty Correlates with Learning Rate in a Go/No-Go Task in Göttingen Minipigs - Nanna Marie Lind; Anette Moustgaard (Neural Plasticity)
Novelty-seeking and harm-avoidance personality traits influence Go/No-go (GNG) learning in humans. Animal studies have also indicated a link between response to novelty and spatial discrimination learning. In the present study, we test the hypothesis that learning rate in a GNG task correlates with the behavioral response of Göttingen minipigs to novelty. In a group of 12 minipigs of mixed genders, response to novelty was measured by numbers of contacts with a novel object, and the total duration of exploration of the novel object. These parameters were correlated to individual learning rate in a GNG task. The number of sessions to reach criterion in the GNG task correlated significantly with the number of contacts to a novel object (r = 0.70, p = 0.03), but not with the duration of object exploration (r = 0.29, p = 0.41). Thus, pigs with a low behavioral response to novelty learned the GNG task faster than did pigs with a strong behavioral response to novelty, indicated by the tendency to approach novel objects. We hypothesize that the critical factor in this relation is difference in emotional reactivity rather than difference in motivation for exploration. In conclusion, in addition to ‘cognitive’ ability, ‘temperamental’ factors are likely to influence learning in individual pigs.